Concussões recorrentes imediatamente após exercício físico de natação ocasionam neuroinflamação e diminuem a cognição de ratos jovens - Cassol, Gustavo (2018)
Concussion is a change in brain function, caused by acceleration and deceleration of the sudden brain. It is closely linked to football, NFL and rugby sports, often occurring in adolescence. Little is known about the effects of recurrent concussions in adolescents, especially with the sum of stress caused by physical exercise. In this way, young rats with 41 days old were submitted to a physical exercise period of five weeks, where two concussions were performed each week, on the second and fifth days, immediately after swimming. Seventy-two hours after the last concussion, we conducted the behavioral tests, such as open field, object recognition and barnes maze. Twenty-four hours after the last behavioral test, the animals were euthanized and the hippocampus was removed for further biochemical analyzes for RT-PCR (mRNA NFkB, IL-1β, TNF-α, casp3, nAChR α7, Nfe2l2, BDNF, Ntrk2 and CREB1) and Western Blotting assay (Iba-1, GFAP, TNF-α, caspase-3, nAChR α7, SOD2, mBDNF, TrkB and phospho-CREB). Statistical analysis revealed that recurrent concussions induced cognitive impairment in long-term memory (LTM) in exercise animals. Biochemical analyzes reveal that recurrent concussions induce increased expression of inflammatory and apoptotic genes such as mRNA NFkB, IL-1β and caspase-3 in sedentary rats. In addition, an increase in TNF-α was observed in the animals concussion exercise when compared to sedentary concussion. This shows that, physical exercise did not potentiate the damage caused by concussion in the mRNA of these proteins. The mRNA nAChR α7 was shown to be decreased in the sedentary concussion group in relation to the sedentary control. The mRNA nAChR α7 expression was not potentiated in the concussion exercise group. No statistical difference was seen in the mRNA Nfe2l2. Analysis of anti-inflammatory proteins by Western blotting revealed that, a decrease in nAChR α7 levels in the sedentary concussion group was observed relative to the sedentary control. However, when we evaluated the levels of the antioxidant enzyme SOD2, only the concussion exercise group was shown to be decreased when compared to exercise control. Our data reveal that recurrent concussions do not induce GFAP increase. However, physical exercise potentiated the content of inflammatory proteins such as Iba-1, TNF-α, as well as the apoptotic caspase-3 protein. On the other hand, concussion does not alter the BDNF gene expression, but the mBDNF decreases in the sedentary concussion when compared to the exercise control. Regarding gene expression for TrkB, the Ntrk2 mRNA, both concussion groups were increased relative to the sedentary control, but the concussion effect did not differ in TrkB content. Thus, in both concussion groups the CREB1 mRNA was shown to be increased in relation to the sedentary control, whereas, the amount of phospho-CREB was only decreased in the concussion groups in relation to the exercise control. Our data show that concussion plus physical exercise exhibits an increase in inflammatory proteins, decreasing the amount of some memory-related proteins and that only concussion alone does not exert behavioral damage.